Agricultural output, calories and living standards in England before and during the Industrial Revolution - Morgan Kelly; Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2012)
This paper surveys the results of four recent, separate attempts at estimating agricultural output and food availability in England and Wales at points between the Middle Ages and the Industrial Revolution. It highlights their contrasting implications for trends in economic growth and nutritional status over time. It also offers some suggestions aimed at narrowing gaps between the evidence and how it has been interpreted.
Keywords: N1; N5; 330; agriculture; nutrition; economic growth